Seat Discomfort Of Dutch Truck Driver Seat: A Survey Study And Analysis - Tan, Chee Fai; Chen, Wei; Rauterberg, Matthias (2010)
This paper described a survey that was designed to examine the seat discomfort and travel time factors for Dutch truck driver seat to reduce discomfort. Truck drivers were at risk of body discomfort for long hours sitting, and experience significant discomfort at different body parts. For the truck seat questionnaire, 217 Dutch truck drivers completed self administered questionnaires. Statistical methods were applied to analyze the surveys. Body discomfort level after one hour and five hours were studied. The outcomes from the analytical results were important and required more attention to reduce the body discomfort for long hour sitting.